Restoring Postoperative Natural Killer Cell Function by Targeting the Immunosuppressive Machinery of Surgery-Induced Myeloid Derived Suppressor Cells - Angka, Leonard (Université d'Ottawa / University of Ottawa, 2021)
In the aftermath of cancer surgery, Natural killer (NK) cells are severely suppressed. NK cells are critical for anti-tumour surveillance and their postoperative dysfunction creates an opportunity for metastases. I hypothesized that NK cell suppression is mediated by multiple suppressive mechanisms of surgery-induced Myeloid Derived Suppressor Cells (Sx-MDSCs). In this thesis, I first show that NK cell dysfunction is far worse than previously described. In a cohort of colorectal cancer (CRC) surgery patients (n=42), the ability of NK cells to secrete IFN-gamma in response to stimulation was suppressed for up to 2 months after surgery. Secondly, since Sx-MDSCs have been poorly characterized in humans, I thoroughly phenotyped Sx-MDSCs from cancer surgery patients using flow cytometry (n=32 patient samples) and single-cell RNA sequencing (n=6 patient samples). Additionally, upon screening a library of 150 compounds, I showed that Sx-MDSC rely on PI3K signaling for their suppression of NK cells in ex vivo NK cell suppression assays. The third part of this thesis explores the contribution of Sx-MDSCs to the rapid reduction in postoperative arginine, the perioperative importance of arginine for NK cells, and the therapeutic effects of a perioperative arginine enriched supplement (AES) on metastases in murine models of surgical stress. Here, I showed that perioperative AES attenuates postoperative metastases by accelerating NK cell recovery after surgery. These promising preclinical data combined with evidence from the scientific literature led us to initiate a Phase II randomized-controlled clinical trial assessing the ability of perioperative AES to improve NK cell function after surgery in CRC patients (n=12/arm). In the last part of this thesis, I present the results from our clinical trial, which showed only a transient and, at best, modest improvement in NK cell function. Importantly, this may have been heavily influenced by poor postoperative patient compliance in taking the AES. In conclusion, this body of work describes the multifactorial role that Sx-MDSCs play in mediating postoperative NK cell suppression, and that safe, effective, and targeted perioperative interventions should be further investigated as a strategy to attenuate metastatic disease recurrence after surgery.
Keywords: Immunotherapy; Natural Killer Cells; Myeloid Derived Suppressor Cells; Surgery; Arginine; Perioperative; Immunology; Cancer